Demystifying Serverless Architecture for Scalable Web Applications - Vaibhav Vudayagiri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Serverless computing has revolutionized the development and deployment of scalable web applications by abstracting infrastructure management and enabling automatic scaling. This article aims to demystify serverless architecture by thoroughly analyzing its core concepts, benefits, and practical implementation strategies. We differentiate between Function-as-a-Service (FaaS) and Backend-as-a-Service (BaaS) models and explore how they contribute to scalability and cost efficiency. Deployment best practices are outlined using AWS Lambda, Azure Functions, and Google Cloud Functions. This article addresses common challenges associated with serverless computing, including cold starts and execution time limitations, and propose solutions to mitigate these issues. Integration with DevOps practices is also discussed, demonstrating how serverless applications can be incorporated into continuous integration and continuous deployment (CI/CD) pipelines. Through case studies, this article illustrates the effective utilization of serverless architecture in building scalable and resilient web applications.